ISLAMIC VIEWPOINT ON THE IMPORTANCE AND CHARACTERICS OF KNOWLEDGE - Muhammad Ibrahim Muhammadi; Arshad Munir Leghari (دی اسکالر)
Education is a basic requirement of all human being which leaves them blind and stranded when absent. Allah SWT, who is our creator and sustainer, has not only provided us opportunities to seek knowledge but also told us what is beneficial to learn and what is not. Allah SWT is “العلیم” (All Knowing), “الحکیم ”(The Wise), and  “الخبیر” (The All-Aware). From his unlimited knowledge, He has guided the mankind about the type of knowledge that leads to hikmah, direction, and guidance. It is also important to know that Allah SWT has not only provided human beings with guidance about what is considered to be beneficial knowledge but has also bestowed with the faculties of learning which enable them to pursue knowledge and awareness. However, in this quest of searching for knowledge, the man goes far beyond what can be considered as the Ilm An-Nafia or the beneficial knowledge. What is happening, as a result, is that despite the countless number of sciences and branches of knowledge being pursued and the untamed flow of books and articles each day, the pain and misery of human beings is still prevalent. Wars and bloodshed are still spread all around. Corruption is still prevalent. Political and economic subjugation is still a trend at personal, national as well as international levels. This all earnestly calls us to reconsider the knowledge that we are pursuing and how does it help to solve the problems of humanity. This article is an attempt to reconsider the concept of knowledge and education from the Islamic perspective. Islam, being a universal religion that is not only a religion but a complete code of life, provides us clear guidance on what is beneficial knowledge and what should be our approach towards attaining it.